A comparative photophysical and photoelectrochemical study of undoped and 2-aminothiophene-3-carbonitrile-doped carbon nitride. (20th November 2016) - Díaz-García, Ana Korina; Díez-García, María Isabel; Lana-Villarreal, Teresa; Gómez, Roberto
Graphical abstract: Highlights: The effect of molecular doping on carbon nitride is revealed by means of photoelectrochemical and luminescence measurements. The effect of pH on the photoelectrochemical response of pristine and doped carbon nitride is presented. The intensity of the emission band appearing as a result of molecular doping depends reversibly on the applied potential. Doped carbon nitride exhibits stronger light absorption and enhanced photocurrents for hydrogen generation. Abstract: Introducing molecular dopants in carbon nitride has been shown to dramatically modify its electronic structure, resulting in efficient charge separation and improved photocatalytic efficiency. Herein, we have studied the effect of doping carbon nitride with 2-aminothiophene-3-carbonitrile. A fundamental photoelectrochemical characterization has been performed comparing the behavior of the resulting material (ATCN) with undoped carbon nitride (CN). On the one hand, it is shown that the photocurrent onset shifts with the pH up to a value of 8 for both materials, as expected theoretically. On the other, ATCN, which benefits from additional light absorption, shows an improved photoactivity toward hydrogen evolution. In addition, it displays intriguing photoluminescence properties that can be additionally engineered by modulating the potential. In a more general vein, this study illustrates how to shed light on the effects of introducing molecular dopants in the CN matrix.